Comparison of phytochemical profiles and antiproliferative activities of different proanthocyanidins fractions from Choerospondias axillaris fruit peels. (November 2018) - Li, Qian; Liu, Chengmei; Li, Ti; McClements, David Julian; Fu, Yinxin; Liu, Jiyan
Abstract: Epidemiological studies had indicated that the incidence of colorectal cancer is inversely correlated to the consumption of proanthocyanidins (PAs). In this study, five PAs fractions isolated from Choerospondias axillaris fruit peels with different mean degree of polymerization (mDP) were characterized and their antiproliferative effects on Caco-2 cells were investigated. MALDI-TOF-MS results indicated that PAs fractions were composed of procyanidins with DP up to 13-mers. All PAs fractions induced dose and time-dependent reductions of Caco-2 cell viability. The IC50 values of PAs fractions with increasing mDP were 240 ± 16.0, 143 ± 9.53, 87.0 ± 3.55, 44.3 ± 4.89, and 42.8 ± 2.20 μg/mL after 24 h incubation, respectively. The observed reduction in Caco-2 cell viability was due to apoptosis via the activation of caspase-9, caspase-3, caspase-8 and the elevation of intracellular ROS generation. Moreover, the extent of the reduction in cell viability after exposure to PAs fractions was positively correlated with their mDP and galloylation. These results indicate that Choerospondias axillaris peel is a potential source of natural chemopreventive agents for the treatment of colorectal cancer. Graphical abstract: Highlights: Five PAs fractions isolated from Choerospondias axillaris peels were studied. PAs profiles and structural composition of PAs fractions were analyzed by HPLC and MALDI-TOF-MS. PAs fractions induced a dose and time-dependent reduction of Caco-2 cell viability. The antiproliferative effect of PAs was in a mDP and galloylation dependent manner. The antiproliferative effect was due to the induction of caspase-dependent apoptosis